IMPLEMENTATION OF HEALTH PROMOTION MODEL ON MATERNAL BEHAVIOR IN STUNTING PREVENTION AND CONTROL IN INDONESIA - Estuti, Anak Agung Alit Kirti; Hastuti, Heni; Hartini, Ninik; Sulaeman, Endang Sutisna (Universitas Brawijaya, 2025)
Stunting remains a major public health issue in Indonesia. According to the Indonesian Nutritional Status Survey (SSGI), stunting prevalence decreased from 27.7% (2019) to 19.8% (2024). Despite this progress, behavioral, sociocultural, and structural barriers continue to limit preventive efforts, particularly those related to maternal practices. This study aims to explore the implementation of health promotion by the Stunting Reduction Acceleration Team (TPPS) and how these efforts shape maternal behavior in stunting prevention, interpreted using the Health Belief Model (HBM) framework. A qualitative phenomenological design was applied to explore mothers’ subjective experiences, meaning-making, and perceptions. A total of 30 informants from five sub-districts in Surakarta City were selected purposively, consisting of health workers, cadres, village officials, and community members. Data were collected through in-depth interviews (March-August 2024) and analyzed using qualitative content analysis. Three major themes emerged: Maternal perceptions regarding susceptibility and severity of stunting; Enabling and reinforcing factors influencing maternal preventive behaviors, including family support, digital health information, and government programs; and Perceived barriers related to economic constraints, poor knowledge, and misconceptions. The integration of TPPS activities, Posyandu services, and digital media strengthened cues to action and improved mothers' perceived benefits of prevention. The study highlights gaps in maternal understanding of stunting and identifies specific HBM components that influence preventive behavior. The findings provide new insight on how TPPS health promotion strategies can better target perceptions, barriers, and behavioral cues to improve maternal engagement in stunting prevention. Strengthening cross-sector collaboration and digital-based education is crucial for future intervention models.